PENGEMBANGAN BIG BOOK KEBUN TEH JAMUS BERBASIS METODE GLOBAL UPAYA PENINGKATAN KEMAMPUAN MEMBACA NARASI SISWA - Arifah Sentika Rahmawati; Panca Dewi Purwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low ability to read narrative text in class II elementary school students is caused by the minimal use of learning media that is interesting and appropriate to the characteristics of the students. The aim of this research is to develop, test the feasibility, and test the effectiveness of the Jamus Tea Garden Big Book media based on global methods in improving the reading ability of narrative texts for class II students. This research uses the Research and Development (R&D) method by adapting the Borg & Gall model to the trial use stage. The research subjects consisted of material experts, media experts, teachers, and 26 class II students at Banyubiru State Elementary School. Data collection techniques include observation, questionnaires, as well as pretest and posttest, which are analyzed using the N-Gain test. The validation results show that the media obtained a score of 91.67% from material experts and 90.625% from media experts, which is included in the "Very Decent" category. The effectiveness test shows an increase in students' reading ability with N-Gain of 0.60 in the small group and 0.64 in the large group, which is in the "medium" category. The novelty of this research lies in the development of digital Big Book media which is integrated with the local wisdom of the Jamus Tea Garden and supported by interactive audio features according to global method principles, thereby providing a more contextual and enjoyable learning experience. Thus, the Jamus Tea Garden Big Book media based on global methods was declared feasible and effective for improving the ability to read narrative texts for class II elementary school students.